Development and standardization of a lip-reading test in Kannada language to detect pseudohypacusis - TA, Subba Rao (Journal of All India Institute of Speech and Hearing)
Occas4onaly the patient is not cooperative for audiological evaluation. For this, reasons may vary from not understanding the test procedure to deliberate feigning a hearing loss. The terms ’functional hearing loss’ (Veatry and Chaiklio, 1962) and ’pseudohypacusis’ (Martin, 1978) are used generally to indicate a feigned hearing loss. There are many tests· to detect pseudohypacusis, but there always remains a need for a simpler and more reliable tests to reveal the extent of a functional hearing loss.